To solve the equation 5/3 - 2x = 1/6, we will start by simplifying both sides of the equation.
First, we can simplify the left side by finding a common denominator for 5/3 and 1/6. The common denominator is 6, so we can rewrite 5/3 as (5/3)(2/2) = 10/6.
So, the equation can be rewritten as:
10/6 - 2x = 1/6
Next, we can subtract the fractions on the left side of the equation:
10/6 - 2x = 1/6
9/6 - 2x = 1/6
Now, we can solve for x by isolating the variable. We can do this by subtracting 9/6 from both sides:
-2x = 1/6 - 9/6
-2x = -8/6
Finally, we can simplify the right side of the equation:
-2x = -4/3
To solve for x, we can divide both sides of the equation by -2:
x = (-4/3) / -2
x = 2/3
Therefore, the solution to the equation 5/3 - 2x = 1/6 is x = 2/3.
What is the solution of the equation 5/3−2x=1/6 ?(1 point)
1 answer